Optimisation of extraction methods and rheological characteristics of soursop juice - Quek, Meei Chien (2012)
The optimisation and comparison of various soursop juice extraction methods were investigated through quantitative and qualitative measurements in finding a suitable method for soursop juice processing. The effects of four individual extraction methods at various temperature or power and time combinations on juice yield,ascorbic acid, colour and total soluble solids of soursop juice were studied and optimised based on maximum responses in terms of juice yield, ascorbic acid, colour and total soluble solids. The optimum extraction conditions obtained for cold water blending, hot water blending, hot water extraction and microwave oven extraction were 30 oC, 90 oC, 65 oC for 30 minutes and 850 W for 2 minutes. The four optimised extraction methods for soursop juice above were then compared for the responses of juice yield and ascorbic acid remained. The result obtained shows that the microwave oven extraction method has a greater capability in producing soursop juice. Juice yield was 73%, 93% and 7% higher than those obtained by cold water blending, hot water blending and hot water extraction methods while the ascorbic acid preserved was at least 3% higher. For this reason, the optimised microwave oven extraction method at 850 W and for an extraction time of 2 minutes is recommended for processing of soursop juice in the beverage industry. The flow behaviour and characteristics of soursop juice concentrates were investigated through rheological measurements and modelled using superposition technique by the double shifting method. The rheological studies were carried out using a rheometer with concentric cylindrical geometry over a wide range of temperatures (10-70 oC) and concentrations (10-50 oBrix) at shear rates of 0-400 s-1. The effect of temperature and concentration on rheological behaviour of freeze-dried soursop juice concentrates were investigated. Several rheological models were fitted to the rheological data, namely, Newtonian, Power law, Bingham, Casson and Herschel-Bulkley models. Power law is the best fitted model attributed to its high value of coefficient of determination (R2=0.9989). The soursop juice concentrates exhibited shear thinning or pseudoplastic behaviour with n<1. The consistency coefficients dependency on temperature and concentration were well described by Arrhenius relationship (R2=0.8845) and exponential relationship (R2=0.9851) respectively. The flow activation energy of soursop juice concentrates were 8.32 to 30.48 kJ/mol. The superposition technique has sufficiently modelled the overall rheological characteristics of soursop juice concentrates over a wide range of temperature and concentration into a single master curve using shift factors based on double shifting steps. This technique also showed that the soursop juice concentrates increases in viscosity and pseudoplasticity behaviour with concentration.